Pengaruh Jenis Tanah terhadap Semai Mahoni Daun Besar (Swietenia Macrophylla) - John F. Sahusilawane; Moda Talaohu; Lydia R. Parera (Syntax Corporation, 2023)
Big Leaf Mahogany (Swietenia macrophylla) is a tropical plant commonly found growing wild in teak forests and areas near the coast. This plant is also known for its resilience, meaning it can withstand harsh and arid soil conditions. Even without watering for months, mahogany can still survive. The propagation of this plant can be done through seeds, as well as through air layering or grafting. When used for medicinal purposes, it should not be treated with chemical (inorganic) fertilizers or pesticides. The significance of this research lies in providing valuable information to relevant institutions about the suitable soil type for propagating Big Leaf Mahogany (Swietenia macrophylla) seedlings, ensuring high-quality seedlings for reforestation or afforestation efforts. The research was conducted at the Greenhouse of the Faculty of Agriculture from March to June 2023. The objective of this study was to determine the effect of different soil types on the growth of Big Leaf Mahogany (Swietenia macrophylla) seedlings. The experimental design used in this research was a Completely Randomized Design (CRD) with 2 (two) treatments and 3 (three) replications. The treatments consisted of: A (Regosol soil) and A2 (Podsolik soil). The research results indicate that Regosol soil type provided better average growth results for Big Leaf Mahogany (Swietenia macrophylla) seedlings.